Digital Techniques for Documenting and Preserving Cultural Heritage - Bentkowska-Kafel, Anna; MacDonald, Lindsay (Collection Development, Cultural Heritage, and Digital Humanities, 2018)
In this unique collection the authors present a wide range of interdisciplinary methods to study, document, and conserve material cultural heritage. The methods used serve as exemplars of best practice with a wide variety of cultural heritage objectshaving been recorded, examined, and visualised. The objects range in date, scale, materials, and state of preservation and sopose different research questions and challenges for digitization, conservation, and ontological representation of knowledge. Heritage science and specialist digital technologies are presented in a way approachable to non-scientists, while a separate technical section provides details of methods and techniques, alongside examples of notable applications of spatial and spectral documentation of material cultural heritage, with selected literature and identification of future research. This book is an outcome of interdisciplinary research and debates conducted by the participants of the COST Action TD1201, Colour and Space in Cultural Heritage, 2012-16 and is an Open Access publication available under a CC BY-NC-ND licence.